Pengaruh welas asih diri terhadap beban pengasuhan pada pengasuh individu dengan skizofrenia - Aditya, Nabila; Farisandy, Ellyana Dwi (Konsorsium Psikologi Ilmiah Nusantara, 2025)
Most people with schizophrenia is highly dependent on the involvement of those closest to them, especially their families. Providing care for a long period of time can affect the caregiver's condition and potentially experience caregiver burden and decreased physical and mental health. The purpose of this study is to determine the significant negative effect of self-compassion on caregiver burden in schizophrenia caregivers. This study involved 373 schizophrenia caregiver subjects. The Zarit Burden Interview and the Self-Compassion Scale were employed in this study. The simple linear regression analysis indicated that there is a significant effect of self-compassion in reducing caregiver burden in schizophrenia caregivers. The higher the self-compassion, the lower the caregiver burden perceived by schizophrenia caregivers. These results allow for alternative interventions that consider cultural contexts, such as self-compassion training, based on the development of collective-value strategies, acceptance, and spirituality.